C-reactive Protein of Clinical Outcomes in COVID-19 Basra Patients - Saleh, Alaa A.; Waheed, Saad; Al Sawafi, Abeer (Iraqi Journal of Science, 2023)
By the time we conducted the current study,- COVID-19 epidemic has already become a global challenge, paralyzing socio-economic activity dramatically. Hence , this study aimed to identify the most valuable prognostic indicators for COVID19 patients' early and accurate diagnosis by comparing laboratory biomarkers like C -reactive protein between non-severe and severe groups of patients. Depending on clinical symptoms, ---337 COVID-19 patients were enrolled at the Basra City Hospital from March 29 to April 29,2020 were classified into severe and non severe groups. A total of 337 patients were diagnosed with COVID-19, including 306 (128 males and 178 females) were adult patients, and ---31 (10 male and 21 female) Child & teens patients. The mean age of the adult patients was 42.79±16.22 (age rnage 18-85 years),----- Child & teens patients was 12.23± 4.06. All children and more adults had an initial normal C-reactive protein (CRP) <5 mg/L. CRP in severe group (68.51±66.38) was assigned to 27 adult patients (8.82%), and the differences were high significantly (p <0.05) compared to the noﱟn severe group (24.31±45.26). There were significant differences (p<0.05) between the severe group and non- severe groups in all parameters, including hemoglobin, platelet count, white blood cells (WBCs) count, CRP, ferritin as well as erythrocyte sedimentation rate ″ESR″. ---The results of this study indicated,--- that in the majority of children ----with COVID-19 infection , threre was no increase in CRP levels and other biomarkers.On the other hand, a positive link was found between COVID-19 severity and CRP, ESR, and ferritin levels in adults.